Effect of tree age on the yield, productivity, and chemical composition of essential oil from Cinnamomum burmannii - Anugerah Fajar; Ganjar Abdillah Ammar; Muhammad Hamzah; Robert Manurung; Muhammad Yusuf Abduh (Institut Teknologi Bandung, 2019)
One of the factors that influence the yield of cassia oil is the age of tree. Cassia bark is normally harvested at a tree age of 5 years old and continue to be harvested until 15 years of age. This study investigated the effect of tree age of Cinnamomum burmannii (5, 12 and 20 years old) on the yield, productivity and chemical composition of essential oil from leaf, branch and trunk bark. The essential oil was extracted using steam distillation and liquid-liquid extraction methods. The results showed that the optimum yield of Cinnamomum burmannii oil was obtained when the water content was in the range of 36-47%. The optimum yield of essential oils from the leaf was obtained at 1.36±0.31 wt% (5 years old) and for the branch and the trunk bark were obtained at 3.2±0.07 wt% and 2.95±0.30 wt% (both were 12 years old). Chemical composition of the essential oil was also analysed. The major components of Cinnamomum burmannii oil were determined as cinnamaldehyde (68.3%-82%), cinnamyl acetate (2.5%-16%), cinnamyl alcohol (2.25%-4.6%), and cinnamic acid (3%-8%). The productivity of essential oil was estimated at 336 kg/ha.year (5 years old), 577 kg/ha.year (12 years old) and 387 kg/ha.year (20 years old).